Life's Principle before Materialistic Universe (Global Journal of Science Frontier Research, 2018)
In this paper there is an attempt to prove that the production of the matter in the Universe has been preceded by a life force, a certain principle of life. This vital force gives the meaning to the whole Universe. Without it, the entire material world would have no sense to exist. This way of "thinking" was guaranteed by the existence of the "mislion"; the basic entity of thoughts, ideas, and activity of the presupposed principle of life.